مقارنة بعض معايير تحديد الرتبة لانموذج الانحدار الذاتي (الطبيعي وغير الطبيعي) من الرتبة الاولـى بأستخدام المحاكـاة - عبد الله, سهيل نجم (Journal of Economics and Administrative Sciences, 2010)
The search is contain compared among some order selection criteria  (FPE,AIC,SBC,H-Q) for the Model first order  Autoregressive when the White Noise is follow Normal distribution and some of non Gaussian distributions (Log normal, Exponential and Poisson distribution ) by using Simulation